Psychological distress and experiences of Adolescents and Young Adults with cancer during the COVID‐19 pandemic: A cross‐sectional survey. Issue 4 (5th January 2022) - Glidden, Camille; Howden, Kaitlyn; Romanescu, Razvan G.; Hatala, Andrew; Scott, Ian; Deleemans, Julie M.; Chalifour, Karine; Eaton, Geoff; Gupta, Abha A.; Bolton, James M.; Garland, Sheila N.; Mahar, Alyson L.; et al.
Abstract: Background: This study investigated prevalence of psychological distress, factors associated with distress, and experiences of Adolescents and Young Adults (AYAs) with cancer during the COVID‐19 pandemic. It also compared distress in this group to previously surveyed Canadian AYAs with cancer in 2018 by the Young Adults with Cancer in their Prime (YACPRIME) study. Methods: A cross‐sectional, online, self‐administered survey of AYAs diagnosed with cancer between 15 and 39 years of age was conducted. Psychological distress was measured by the Kessler Psychological Distress Scale (K10). Associations between variables and high psychological distress (K10 ≥ 25), and comparison of prevalence of psychological distress with the YACPRIME study were done using multivariable logistic regression. Summative qualitative content analysis analyzed participant experiences during this pandemic. Results: We included 805 participants. High psychological distress was present in over two‐thirds of the group (68.0%; 95% CI, 64.7%–71.2%). Employment impact during pandemic (AOR (adjusted odds ratio), 2.16; 95% CI, 1.41–3.31) and hematologic malignancy (AOR, 1.76; 95% CI 1.08–2.97) were associated with higher psychological distress, while older age [AOR, 0.95; 95% CI, 0.92–0.99] and personal income < $40, 000 (AOR, 0.38; 95% CI, 0.24–0.58) were associated with lower distress. Adjusted odds of experiencing psychological distress among AYAs with cancer during pandemic compared to pre‐pandemic years was 1.85 (95% CI: 1.36–2.53). Overarching themes of pandemic experiences included: inferior quality of life, impairment of cancer care, COVID‐19 related concerns and extreme social isolation. Conclusion: AYAs diagnosed with cancer are experiencing high psychological distress during this pandemic. Distress screening and evidence‐based interventions to alleviate distress are essential.